Mastering API architecture : design, operate, and evolve API-based systems - Gough, James; Bryant, Daniel; Auburn, Matthew (Sebastopol, CA : O'Reilly, 2022)
"Most organizations with a web presence build and operate APIs; the doorway for customers to interact with the company's services. Designing, building, and managing these critical programs affect everyone in the organization, from engineers and product owners to C-suite executives. But the real challenge for developers and solution architects is creating an API platform from the ground up. With this practical book, you'll learn strategies for building and testing REST APIs that use API gateways to combine offerings at the microservice level. Authors James Gough, Daniel Bryant, and Matthew Auburn demonstrate how simple additions to this infrastructure can help engineers and organizations migrate to the cloud; and open the opportunity to connect internal services using technologies like a service mesh." --
Designing, building, and testing APIs. Design, build and specify APIs -- Testing APIs -- API traffic management. API gateways: ingress traffic management -- Service mesh: service-to-service traffic management -- API operations and security. Deploying and releasing APIs -- Operational security: threat modeling for APIs -- API authentication and authorization -- Evolutionary architecture with APIs. Redesigning applications to API-driven architectures -- Using API infrastructure to evolve toward cloud platforms -- Wrap-up.
Formerly CIP.
Includes bibliographical references and index.
Keywords: Application program interfaces (Computer software); Computer programming -- Management